Teachers’ motivation for teaching in higher education: Portuguese validation of a questionnaire - Almeida, Leandro S. (2021)
Motivation for teaching is key in the establishment and further development of high-quality higher education, as it affects teachers’ investment in quality learning experiences for their students, as well as institutional efficacy and well-being. This study aimed to validate a questionnaire, originally developed in Belgium, designed to evaluate three dimensions (self-efficacy, interest, and effort) of intrinsic motivation for teaching for a different national population. The sample consisted of 616 academics working in public higher education institutions in Portugal. Confirmatory factor analysis was conducted and internal consistency of items analyzed. The results show that the original dimensionality of the construct is confirmed in the Portuguese teachers’ sample. Motivation for teaching in the Portuguese context is primarily explained by the following factors: personal efficacy, interest in the task, and effort placed on teaching responsibilities. A difference was found in that personal efficacy could not be divided in context and general personal efficacy.